Use of Networks by Incubator Tenants to Acquire Knowledge to Create Businesses in University Incubation Centres in Kenya - Nkoroi, Lillian; Mutwiri, Caroline; Njoroge, Rose (International Journal of Innovative Research and Knowledge, 2020)
The purpose of this paper is to analyze critically the Use of Networks by Incubator Tenants to Acquire Knowledge to Create Businesses in University Incubation Centres in Kenya. The methodology for the study is mixed methods including Document analysis, interviews, administration and analysis of questionnaires to obtain data from incubation centres in Kenyatta University and Strathmore University. The study revealed that the tenants of incubation centres relied on internal networks comprising of other tenants, academia and alumni to acquire and use knowledge for their businesses. External networks were organized on need basis by the incubation centre and therefore knowledge acquisition from such networks was only to a limited extent. The paper has significant theoretical, policy, and practical implications. From a theoretical perspective, the study finds that tenants in university business incubation centres have a high propensity for informal networks as opposed to the formal networks set up by the management of incubation centres.
Keywords: knowledge networks; university incubation centres